2015
DOI: 10.1371/journal.pone.0126319
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Localization and Tumor Suppressor Function of Epithelial Tissue-Specific Transcription Factor ESE3 in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal cancer is one of the most common malignant cancers worldwide. The molecular mechanism of esophageal squamous cell carcinoma (ESCC) is still poorly understood. ESE3 is a member of the Ets transcription family, which is only expressed in epithelial tissues and acts as a tumor suppressor gene in prostate cancer. Our study aim was to confirm whether ESE3 is involved in the carcinogenesis of ESCC. Immunohistochemical analysis revealed that ESE3 was mainly located in cell nuclei of normal tissues and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
(19 reference statements)
0
12
2
Order By: Relevance
“…EHF has been demonstrated to be a potential tumor-suppressor in prostate cancer and ESCC, 19, 22, 23 whereas our data suggest that EHF may be a functional oncogene in gastric cancer. We thus speculate that EHF derived from different types of cells or tissues has strikingly distinct functional activities in tumorigenesis.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…EHF has been demonstrated to be a potential tumor-suppressor in prostate cancer and ESCC, 19, 22, 23 whereas our data suggest that EHF may be a functional oncogene in gastric cancer. We thus speculate that EHF derived from different types of cells or tissues has strikingly distinct functional activities in tumorigenesis.…”
Section: Discussioncontrasting
confidence: 50%
“…18, 19, 20 Moreover, EHF may regulate epithelial growth and differentiation and have an important role in oncogenesis of epithelium-derived tumors. 18, 21 EHF has been demonstrated to function as a potential tumor suppressor gene in prostate cancer and esophageal squamous cell carcinoma (ESCC), 19, 22, 23 and be frequently downregulated by promoter methylation. 22 On the other hand, it is overexpressed in ovarian and mammary cancers 24, 25, 26 and may be a predictive marker for poor survival in ovarian cancer.…”
mentioning
confidence: 99%
“…In oesophageal squamous cell carcinoma (ESCC), the primary mechanism of EHF protein dysregulation is altered subcellular localization, where in contrast to its predominantly nuclear expression in the normal oesophageal epithelium, EHF is localized to the cytoplasm. While the mechanisms driving the cytoplasmic localization of EHF are yet to be defined, re-expression of EHF in ESCC cell lines which restored its nuclear expression, inhibited cell proliferation, colony formation, migration, and invasion [ 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…Authors have reported loss of ESE3 expression in esophageal squamous cell carcinoma (17) and prostate tumor (13,15,16) cases. We found that ESE3 expression levels were lower in PDACs than in matched normal pancreatic tissue specimens.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of ETS factors known as epithelium-specific ETS (ESE) factors, including ESE1 (Ert/Jen/Elf3/Esx), ESE2 (Elf5), ESE3 (EHF), and Pdef (Pse), are expressed in epithelial tissues (12). Authors reported that ESE3 in particular binds directly to target genes to control epithelial-to-mesenchymal transition (EMT), stem-like features (13,14), and tumor progression (1517). Feldman and coworkers have analyzed the expression patterns of ESE factors in diverse types of tissues and cell lines, and found that in normal human pancreas only ESE1 and ESE3 but not ESE2 and Pdef proteins are expressed (5).…”
Section: Introductionmentioning
confidence: 99%